Preparing of chemical bonding learning media based android using smart apps creator program - Ramlan Silaban; Osi Annauli Br Girsang; Roselva Theresia Manalu; Marham Sitorus; Simson Tarigan; Irving Josafat Alexander (Jurnal Pendidikan Kimia (JPKIM), 2023)
The aim of this research is to obtain Android-based chemical bond learning media using the smart apps creator program that is feasible and eligible to use. To achieve the goal, development research has been carried out which refers to the 4 D model with the stages define, design, develop and disseminate. The research was conducted at SMA Negeri 5 Medan involving teachers and students of class X MIA. The research instruments used are non-test instruments including needs analysis instruments, feasibility test instruments and student response instruments. The research results are: (1). An Android-based chemical bond learning media has been obtained using a smart apps creator program with features main view, main menu, learning material, evaluation, summary and references. (2). The Android-based chemical bond learning media obtained was deemed suitable for use in learning with a feasibility level of 85.0% with very worthy category. (3). The students give good eligibility responded (82.6%) for the Android-based chemical bond learning media obtained with meets the requirements for use as learning media.Keywords: Android based; Chemical bonding; Learning media; Smart apps creator program